2016
DOI: 10.1038/boneres.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Application of platelet-rich plasma with stem cells in bone and periodontal tissue engineering

Abstract: Presently, there is a high paucity of bone grafts in the United States and worldwide. Regenerating bone is of prime concern due to the current demand of bone grafts and the increasing number of diseases causing bone loss. Autogenous bone is the present gold standard of bone regeneration. However, disadvantages like donor site morbidity and its decreased availability limit its use. Even allografts and synthetic grafting materials have their own limitations. As certain specific stem cells can be directed to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 219 publications
(124 reference statements)
2
116
0
1
Order By: Relevance
“…The action of these preparations relies on the secretion of a cocktail of proteins from platelet-α-granules. As autologous formulations, prepared via relatively simple chairside fabrication, these blood products have recently generated considerable interest in clinical regenerative medicine [2][3][4][5]. Growth factors, such as insulin-like growth factor-1 (IGF-I), platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), epidermal growth factor (EGF), platelet-derived epidermal growth factor (PDEGF) and fibrin matrix proteins, are found in these preparations at a higher concentration than in blood, and have been proposed to directly contribute to accelerating tissue regeneration [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The action of these preparations relies on the secretion of a cocktail of proteins from platelet-α-granules. As autologous formulations, prepared via relatively simple chairside fabrication, these blood products have recently generated considerable interest in clinical regenerative medicine [2][3][4][5]. Growth factors, such as insulin-like growth factor-1 (IGF-I), platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), epidermal growth factor (EGF), platelet-derived epidermal growth factor (PDEGF) and fibrin matrix proteins, are found in these preparations at a higher concentration than in blood, and have been proposed to directly contribute to accelerating tissue regeneration [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The PRP was used for cell culture experiments at a final concentration of 2.5% in the culture medium, whereas PRF was used at a concentration of 5% according to the results of the pre‐investigation. Concentrations chosen are consistent with those used by Choi et al and Fernandes and Yang . Zoledronate (ZA; Zoledronsäure HEXAL® 4 mg/5 mL) was obtained in sterile 4 mg/5 mL intravenous infusion form.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the Factors and Genes Are Shown in Osteogenesis. 20 been demonstrated that the activation of CDK1 promotes osteogenic differentiation of MSCs through phosphorylation of EZH2, the catalytic subunit of PRC2, that in turn catalyzes the methylation of histone H3 on lysine 27 (H3K27). 24 However, epigenetic mechanisms are not limited to the following.…”
Section: Personalized Bone Regenerationmentioning
confidence: 99%